Neurociências na escola: estudo sobre a persistência da memória semântica nos anos finais do Ensino Fundamental - Sasha Luisa de Azevedo Nunes (2017)
Memory is one of the most essential individual capacities; which builds our sense of self and the perception of the world around us. Learning and memory are closely related neurobiological processes, with learning being the process by which we form knowledge, while memory is the process in which this knowledge is encoded, consolidated and subsequently retrieved. The perception of the interaction between learning and memory demonstrates the importance of memory in the classroom. . Some research highlights the relation of a good memory with a good academic performance, but few evaluate the longterm memory related to the disciplinary contents. The present dissertation intends to investigate the effect of thematic revisit on the persistence of semantic memory in elementary school students, thus testing if the memory lasts more when semantic components of the content of a class are presented to the students in a second class temporarily next. To test this hypothesis, after a science class, one group of students will attend classes normally and the other will attend classes with content worked on the same theme. The subjects were students (between 12 and 16 years old) of last years of high school of a public school, named Groups A, B, C and 9 year. To evaluate the semantic memory relative to the new content, we elaborated memory tests from the principles of recall and recognition. We recorded the classes in video and audio with the objective of assisting in the interpretation of the data collected. Group A attended the Science Class (SC) on Nervous System (NS) class followed by a standard Portuguese class. Group B attended the same SC, but in the Portuguese class, they worked on the text on the effects of drugs in the NS. The questionnaires were validated in Group C. All the students performed a first test (called pre-lesson) to evaluate their previous knowledge about the subject NS. The memory related to learning the NS class was accessed shortly after the Portuguese class (T1) and the following day (T2). In Group C, the memory was also measured with 7 (T3) and 21 days after class to evaluate the persistence of memory. Our results showed that the duration of memory on school contents lasts long time as observed in the Group C tests up to 21 days after the class and in the 9 year, one year after class. Student performance was significantly better in T1 and T2 compared to pre-class. However, there was no difference between groups A and B. However, when we categorized the issues into easy and difficult, we observed a significant improvement in T1 and T2 only in group B related difficult questions, compared to performance in the pre-class. In order to verify if the intervention would be able to benefit the application of the memories in problem situations, we elaborated a second questionnaire, in which showed no difference in performance between Groups A and B. We used the analysis of the graph parameters to evaluate the discursive questions of the questionnaires: nodes, LCC (largest connected component) and LSC (largest strongly connected component). Nodes represent the number of different words in the responses and LCC and LSC demonstrate the connectivity of speech. In group B, we observed an increase in nodes and LCC in the T1, indicating greater diversity and lexical connectivity in the representation of the memories related to thematic revisit. In addition, the LSC measured in the Science questionnaire showed correlation with the Portuguese performance, reflecting an indirect measure of performance in this discipline. With these results, we demonstrated that the association of the disciplines was able to potentiate memories related to the most difficult questions about the classes. Revisiting the topic has increased lexical diversity and the connectivity of student memory representation, thus demonstrating that it is a form of education that teachers should revisited and be rethought during the structuring of school schedules